Correction: Knockdown of the Sodium-Dependent Phosphate Co-Transporter 2b (NPT2b) Suppresses Lung Tumorigenesis. - Seong-Ho Hong (PLoS ONE, 2014)
[This corrects the article DOI: 10.1371/journal.pone.0077121.].